The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1074/jbc.m110.101014
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Cysteine 346 Is Essentially Involved in Regulating Panx1 Channel Activity

Abstract: Pannexins constitute a family of proteins exhibiting predominantly hemichannel activity. Pannexin channels have been suggested to participate in a wide spectrum of biological functions such as propagation of calcium waves, release of IL-1␤, and responses to ischemic conditions. At present, the molecular mechanisms regulating pannexin hemichannel activity are essentially unknown. Because cysteines have been shown to constitute key elements in regulating hemichannel properties of the connexin-type we performed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…For example, we found that a synthetic peptide containing just this sequence was not sufficient to block current from truncated hPANX1 channels, whereas larger C-terminal proteins were effective. In addition, a more proximal C-terminal residue (Cys-347) that regulates basal channel activity has been identified (16). It is also interesting that hPANX1 inhibition associated with mutations in this restricted region or obtained by cell-free reconstitution of C-terminal proteins with truncated channels was most pronounced at hyperpolarized potentials.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, we found that a synthetic peptide containing just this sequence was not sufficient to block current from truncated hPANX1 channels, whereas larger C-terminal proteins were effective. In addition, a more proximal C-terminal residue (Cys-347) that regulates basal channel activity has been identified (16). It is also interesting that hPANX1 inhibition associated with mutations in this restricted region or obtained by cell-free reconstitution of C-terminal proteins with truncated channels was most pronounced at hyperpolarized potentials.…”
Section: Discussionmentioning
confidence: 90%
“…mSpo20 (14) and PLC␦-PH (15)). Likewise, hPANX1⌬371 currents were unaffected by a Cterminal construct that includes a point mutation (hPANX1(Ct)C347S) known to yield constitutive currents in full-length hPANX1 channels (16). Finally, a C-terminal construct truncated at Glu-391 (hPANX1(Ct)⌬391) provided a block of current that was comparable with that seen with the full-length C terminus, consistent with our observation that residues downstream of Glu-391 are not required for C-terminal inhibition of hPANX1 (cf.…”
Section: C-terminal Cleavage Activates Plasma Membrane Hpanx1mentioning
confidence: 99%
“…31,32 Moreover, there is a loss of channel function when any of the four extracellular cysteines of Panx1 are mutated. 33 The possibility of intrinsic control of pannexin channel activity by the cysteines hints at the potential regulation of the channel by such post-translational modifications as glutathionation or S-nitrosylation.…”
Section: Post-translational Modification Of Pannexinsmentioning
confidence: 99%
“…Interestingly, the two sites that we identified as critical for this inhibitory modification --C40 and C346 --were previously reported to enhance activity of Panx1 channels in mutagenesis studies [259,260]. In that other work, serine substitution at either C40 [260] or C346 [259] produced "leaky" or constitutively active channels. Together with our results, these observations suggest that C40 and C346 may be localized to regions that are important for dynamic up-and downregulation of Panx1 channel activity.…”
Section: Discussionmentioning
confidence: 81%
“…Also, a previous study identified a loss in the Gly2 species in functional, plasma membrane-localized Panx1C346S [259].…”
Section: Discussionmentioning
confidence: 99%